A bibliometric study of ASEAN literature on agricultural biotechnology research 2003-2013 / Sedigheh Famil Dardashti - Sedigheh Famil , Dardashti (2018)
ASEAN (Association of Southeast Asian Nations) is a geo-political and economic organization of ten countries which is located in Southeast Asia with an average of 6 percent per annum Growth Domestic Product (GDP) growth over the past 15 years. The agricultural industry is the mother industry to accelerate ASEAN countries' economic growth besides regional stability. Due to the importance of agriculture in sustainability of the ASEAN countries, this study applied bibliometric methods to evaluate agricultural biotechnology research situation (due to its key role in food productivity and sustainability) among ASEAN scholars, institutes, and countries. To fulfill this, the required data were extracted from the Web of Science (WoS) database for all ASEAN countries in the field of Agricultural Biotechnology during the period 2003 to 2013. In addition, the economic data including total GDP and the share of agriculture in total GDP were collected through World Bank Database for all ASEAN countries during 2003 to 2013. To analyze the data, the Statistical Product and Service Solutions (SPSS) were applied to illustrate both descriptive statistics (frequency, average) and inferential statistics (Correlation Coefficient). The 753 papers in agricultural biotechnology were calculated for all countries during 2003 to 2013. Malaysia with 37 percent of total publication in agricultural biotechnology, had the highest number of publication followed by Thailand with 33.1 percent and Singapore with 14.2 percent which indicated the highest papers were published by these countries. The results showed that the number of published papers among ASEAN countries were significantly different according to year. The results for total number of citation indicated that Malaysian papers had the highest number of citation (7012) followed by Thailand (5284). Malaysia had the highest number (35.4%) of involved institution and organization, followed by Thailand (31.6%). Among top 92 authors who had more than 4 papers, Malaysia had the highest frequency of authors (50%) followed by Thailand (26.1%) and Singapore (17.4%). Findings for relationship between GDP and research output among ASEAN countries showed that there was a positive relationship for all countries except Cambodia and Myanmar. The highest correlation coefficient between GDP and number of publication was observed for Thailand (r=0.928) and Malaysia (r=0.911).